Analisis Faktor-Faktor Yang Mempengaruhi Kinerja Dosen Negeri Pada Kopertis Wilayah V Yogyakarta - Pramudyo, Anung (Universitas Muhammadiyah Yogyakarta, 2010)
This study examines the analysis factors that influence lecture’s performance at Kopertis V Yogyakarta. Based on theory, several variables has been constructed. They are motivation, competency, leadership, and work environment justice are predictors of performance. This research was executed in Kopertis V Yogyakarta with 150 participants. The results supported motivation, competency, and leadership justice has strong predictive to lecture’s performance, but work environment has not influence to lecture’s performance at Kopertis V Yogyakarta.